2007
DOI: 10.1210/en.2006-0792
|View full text |Cite
|
Sign up to set email alerts
|

N-Procalcitonin: Central Effects on Feeding and Energy Homeostasis in Rats

Abstract: Procalcitonin (PCT), the precursor of calcitonin (CT), is a 116-amino-acid peptide, but PCT itself has no known activity. However, although the C cells of the thyroid gland are the dominant source of circulating CT, PCT and its free bioactive amino-terminal fragment (N-PCT) have been localized in adipocytes and neuroendocrine cells as well as in some hypothalamic regions of primary importance in the regulation of feeding and energy balance. These findings together with the coelaboration of N-PCT and CT, and N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 46 publications
4
47
1
Order By: Relevance
“…One very recent study attributes an anorectic effect to amino-PCT (N-PCT), the biologically active fragment of PCT. It has been shown that administration of N-PCT to free-feeding, freely moving unstressed rats significantly reduced food intake in a dose-dependent manner and decreased body weight gain [11]. In the present study, body weight gain during intensive phase tended more towards the desirable gain of 5 % in the study group with a lower increase in serum PCT than in the group with a higher increase in the prohormone.…”
Section: Groupscontrasting
confidence: 42%
See 2 more Smart Citations
“…One very recent study attributes an anorectic effect to amino-PCT (N-PCT), the biologically active fragment of PCT. It has been shown that administration of N-PCT to free-feeding, freely moving unstressed rats significantly reduced food intake in a dose-dependent manner and decreased body weight gain [11]. In the present study, body weight gain during intensive phase tended more towards the desirable gain of 5 % in the study group with a lower increase in serum PCT than in the group with a higher increase in the prohormone.…”
Section: Groupscontrasting
confidence: 42%
“…However, although in group 1b serum PCT increased and in group 2a the prohormone decreased at the end of intensive phase, percentage body weight gain in group 1b was better than in group 2a. Tavares et al [11] mention in their study that the anorectic effect of N-PCT was extremely potent at even low doses but comparatively less significant at the highest dose. Their study suggests that the central receptors mediating N-PCTs anorectic effect were already fully activated at lower doses.…”
Section: Groupsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, c-Fos expression, a marker of neuronal activity, was observed primarily within the ARC and PVN after icv injection of N-PCT (54, 57). In vitro and in vivo studies suggest that N-PCT, similarly to other neuropeptides of the CT family, like amylin and CT gene-related peptides, can function as a ligand for the 55,57). Together, these findings suggest that the anorectic actions of N-PCT likely occur within the hypothalamus.…”
mentioning
confidence: 90%
“…Although CT has been considered as an enigmatic hormone (19), and there is not a true ligand for CT-R, N-PCT has the potential to be an endogenous ligand for central CT-R. Recent evidence indicates that N-PCT can function as a ligand for the CT-R and may act as an anorectic signaling molecule in the CNS (47,54,55).The CT-R has been cloned and characterized in different cell types and species (40). Two CT-R isoforms, CTa and CTb, have been described in the rat brain with an overlapping distribution pattern particularly in hypothalamic nuclei involved in feeding behavior, including the arcuate nucleus (ARC) and the paraventricular nucleus (PVN) (4,23,48).…”
mentioning
confidence: 99%